Ancient Greek Atheism? A Note on Terminological Anachronisms in the Study of Ancient Greek ‘Religion’ - Roubekas, Nickolas P. (Revista Ciências da Religião - História e Sociedade, 2014)
During the last forty years, religion as a concept has bedeviled scholars not only in defining the term, which certainly goes way back in history, but also regarding its applicability as a first-order scholarly tool. Some have argued to dismiss the term altogether, others have sough to re-approach how the term is used, while other scholars have endorsed its usage but based on scholarly stipulative definitions. Recently, further discussions have emerged regarding whether contemporary scholars can use the category ‘religion’ to talk about ancient traditions and classifications. While the issue of anachronisms is undoubtedly present in such debates, the term ‘atheism’ has not been approached in a similar manner. What classical studies on ancient ‘religions’ often lack is a theoretical background already available in the discipline of religious studies. This brief article seeks to open the path for further examination of the place of ‘atheism’ in antiquity based on the problem of applying the term with its modern content and meaning to the ancient world. Even though this study is not exhaustive by all means, its aim is to alert both classicists and historians of religion of the pitfalls neatly hidden behind the scholarly tools often adopted for the description of practices, beliefs, and movements in the ancient world.